The Relationship between Human Resources Management Functions and Job Burnout from the Perspective of Managers and Staff in Deputy of Health in Iran University of Medical Sciences - Farshid Nasrolah Beigi; Pouran Raeissi; Farbod Ebadifard Azar (Tehran University of Medical Sciences, 2021)
Background and Aim: Burnout is one of the most important factors that reduces the productivity of personnel. Therefore, this study aimed to determine the relationship between human resources management functions and job burnout from the perspective of managers and staff of deputy of Health in Iran University of Medical Sciences. Materials and Methods: Subjects of this cross-sectional study consisted of 657 managers and staff members of deputy of Health in Iran University of Medical Sciences that 242 individuals were selected according to Morgan's table as the study population. Research data were collected using two questionnaires of burnout and human resources management functions. Results: 174 (70.7%) participants in the study were women, with mean age and work experience of 41.3 and 15.8 respectively and a standard deviation of 7.35 years. 78.9% of married people and 69.1% of the participants were dissatisfied with the status of their salaries. The dimensions of consequential evaluation, transparent job description and comprehensive training with averages of 4.17, 4.12 and 4.03 out of 7 had the highest score among the various dimensions of human resources functions. Different dimensions of burnout showed that the highest mean was related to feelings of personal inadequacy and depersonalization (4.72). The results of the Pearson correlation test showed that there was a statistically significant relationship between human resources management functions and burnout with a correlation coefficient of -0.439 (P <0.05). Conclusion: Job burnout can be significantly reduced with the improvement of human resources management functions.